ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI RELAKSASI BENSON DAN GENGGAM JARI TERHADAP NYERI IBU POST SEKSIO SESAREA - Christin Natalia (2022)
Cesarean section is the process of removing the fetus and placenta through a surgical process by making an incision in the abdominal wall. One of the impacts caused by surgery is that someone will feel pain, which pain can have an impact on disrupting bonding attachments, disrupting activities of daily living, limited mobilization, and not fulfilling early breastfeeding initiation which results in not optimal breastfeeding. Cesarean section will generally cause higher pain when compared to normal delivery. One of the non-pharmacological therapies to treat pain is Benson relaxation and finger gripping. Stimulation can inhibit pain impulses. Objective: To determine the effect of Benson relaxation and finger gripping on post-cesarean section pain. This study used the literature review method with the application of evidence-based nursing in nursing care for two post-cesarean patients. The instrument used to measure pain in post-cesarean mothers was using NRS (Numeric Rating Scale). Results: there was a decrease in the intensity of pain felt by post-cesarean section mothers after being given non-pharmacological therapy to NRS 3. Keywords: Cesarean section, Benson relaxation, finger grip relaxation